MSMEs Recovery after the COVID-19 Pandemic through Profit-Sharing System - Taudlikhul Afkar; Fauziyah Fauziyah (Universitas Pendidikan Ganesha, 2023)
This research aims to analyze the recovery of MSMEs after the COVID-19 pandemic through a profit-sharing system from the perspective of MSMEs actors. The urgency of this research is because the impact of COVID-19 on MSMEs is very significant on the ability to earn profits, so it is necessary to analyze MSMEs' recovery. The research used a quantitative approach with a population of 260,762 MSMEs in Surabaya; 100 samples were taken using an accidental random sampling technique. Data collection techniques use documentation through questionnaires. MSME recovery is an endogenous variable, the principle of profit-sharing distribution is a mediating variable, and the profit-sharing system (musharakah contract) is an exogenous variable. The data analysis technique used is Partial Least Square (PLS). The research findings show that MSME recovery can be carried out using a profit-sharing system with musharakah contract and mediated by the principle of profit-sharing distribution. The existence of a profit-sharing system carried out with musharakah contract can give confidence to MSME actors to collaborate with sharia financial institutions where there is profit-sharing based on an agreement. If losses occur, they are borne together based on the portion of capital paid in.